Hubungan antara Kebiasaan Belajar dengan Hasil Belajar Siswa pada Mata Pelajaran PAI di SMKS Pembangunan Bukittinggi - Tiya Desmita; Muhiddinur Kamal (Lembaga Yasin AlSys, 2026)
Although the relationship between study habits and student learning outcomes has been widely examined, research specifically analyzing the relationship between these two variables in Islamic Religious Education at the vocational high school level remains relatively limited. This study aimed to analyze the relationship between study habits and student learning outcomes in Islamic Religious Education at SMKS Pembangunan Bukittinggi. The study employed a quantitative approach with a correlational design and involved 109 tenth-grade students selected through total sampling. Data were collected using a study habits questionnaire and documentation of Midterm Examination scores in Islamic Religious Education. The data were analyzed using descriptive statistics, prerequisite analysis tests, and Spearman’s rank correlation test. The results showed a positive and significant relationship between study habits and student learning outcomes, with a correlation coefficient of 0.724, which was categorized as strong, and a significance value of 0.001 < 0.05. The coefficient of determination showed that study habits contributed 52.42% to learning outcomes, while the remaining 47.58% was influenced by other factors outside the scope of the study. These findings confirm that regular and disciplined study habits play an important role in improving student learning outcomes. This study contributes to the development of research on Islamic Religious Education and provides practical implications for teachers, schools, parents, and students in developing effective study habits to improve learning outcomes. Future research is recommended to examine other factors influencing learning outcomes using broader geographical coverage and larger samples.